The Impact of Active Learning Method on Academic Achievement, Motivation, and Attitudes Towards Mathematics - Ghazal, Mostafa Hadi; Nadi, Mohammad Ali; Sahib Kazem, Saleh; Mosavi, Faranak Sadat (International Journal of Education and Cognitive Sciences, 2022)
Purpose: The present study aimed to examine the effect of the active learning method on students' academic achievement, motivation, and attitudes towards mathematics. Methods and Materials: This quasi-experimental study employed a pre-test, post-test design with a control group. The study population consisted of fourth-grade students from the city of Babel in Iraq during the year 2023. Using Cochran's formula, 64 students were selected as the sample, chosen through convenient sampling, and randomly assigned into two groups of 32 students each: experimental and control. The experimental group received active learning instruction, while the control group was taught using traditional methods. The data collection instruments included the mathematical achievement motivation questionnaire by Aminefar and Saleh-Sadeqpour (2009) and the attitude towards mathematics questionnaire by Lim and Chapman (2013). Initially, both groups were informed about the study and a pre-test was administered. The control group was taught using lecture-based instruction, while the experimental group was taught using active learning platforms. The study lasted for six weeks. After the study period, a post-test was administered to both groups, and the results were analyzed using MANOVA to assess the significance of the differences between the two teaching methods. Findings: The results indicated that students in the experimental group, who received active learning, showed greater academic progress. However, no significant differences in attitudes or motivation were found between the experimental and control groups. Conclusion: The results indicated that active learning method can be used to improve students’ academic achievement, motivation and attitudes towards mathematics.